Impression management tactics in Covid-19 related disclosures: A study on the annual reports of Bangladeshi listed insurance companies - Dewan Mahboob Hossain; Md. Saiful Alam; Mohammed Mehadi Masud Mazumder (Asian Journal of Economics and Banking (AJEB), 2023)
Purpose - The purpose of this article is to explore the impression management practices in Covid-19 related discourses in the annual reports of the insurance companies in Bangladesh. Design/methodology/approach - To fulfil this objective, the authors have conducted a discourse analysis of the Covid-19 related corporate narratives in the latest annual reports of listed insurance companies. The findings are then interpreted through the lens of impression management theory, following the impression management strategies identified by Caliskan et al. (2021). Findings - It is found that companies tried to manage the impression of the stakeholders through the strategic use of language. There is evidence that the companies used assertive and performance-oriented tactics to impress their stakeholders. In few cases, defensive strategies were applied. Practical implications -This study will facilitate improving the understanding of corporate communication during the Covid-19 crisis. Policymakers will be able to understand the current status of Covid-19 related disclosures and consider the necessity to provide guidance that may lead to better accountability during the crisis. Originality/value - This study will contribute to the limited literature on Covid-19 related disclosure from the context of developing economies. This research is methodologically novel as it applies discourse analysis and interprets the findings through the lens of impression management.
Keywords: 330; Covid-19; Impression management; Insurance companies; Bangladesh